Age and Sex Association with Metabolic Syndrome among Adults in Sharjah, UAE - Harfil, Sondos; Abuodeh, Raed; M. Abdel Rahman, Wael; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Jan Mohamed, Hamid Jan (Wolters Kluwer - Medknow, 2023)
Background: Metabolic syndrome (MetS) is a significant public health concern associated with a cluster of severe metabolic disorders, such as dyslipidaemia, hypertension and glucose intolerance. Aims and Objectives: This study aimed to investigate the association of age and sex with MetS in a healthy adult population in Sharjah, UAE. Materials and Methods: Two hundred and seventy‑two participants were enrolled and screened for their sociodemographic, anthropometric measurements, body composition analysis (BCA.) and biochemical characteristics. Results: The participants’ mean age was 35.1 years. There were no significant differences in MetS prevalence between the two age groups (<40 vs. ≥40) years. Sex had a significant effect on the MetS. Males had a 3.08 times chance to develop MetS compared to females (adjusted odds ratio = 30.8; 95% confidence interval = [1.65–5.75]). Fat percentage (34.40 [11.20] vs. 24.70 [9.30], P < 0.001) and fat mass (23.60 [15.90] vs. 19.90 [12.30], P = 0.002) were significantly higher in females than in males. All other BCA measurements were significantly higher in males than in females (P < 0.001). Most of the biochemical characteristics were significantly higher in males than in females (P < 0.05), except high‑density lipoprotein level, which was higher in females than in males (P < 0.001). Three MetS components were significantly more prevalent in males than in females: high blood pressure (56% vs. 22%, P < 0.001), high triglyceride (14% vs. 4%, P = 0.002) and high fasting blood sugar (46% vs. 21%, P < 0.001). Conclusions: MetS prevalence was significantly higher in males than in females (36% vs. 18%, P = 0.001). Age does not affect the prevalence of Mets in the study population.